2018
DOI: 10.3389/fmed.2017.00239
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Tolerance, Pregnancy, and Preeclampsia: The Roles of Semen Microbes and the Father†

Abstract: Although it is widely considered, in many cases, to involve two separable stages (poor placentation followed by oxidative stress/inflammation), the precise originating causes of preeclampsia (PE) remain elusive. We have previously brought together some of the considerable evidence that a (dormant) microbial component is commonly a significant part of its etiology. However, apart from recognizing, consistent with this view, that the many inflammatory markers of PE are also increased in infection, we had little … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 830 publications
(564 reference statements)
0
47
0
Order By: Relevance
“…Interestingly, ERG is also present in seminal fluid (394)(395)(396) and human breast milk (6) . Any possible correlation with male fertility (397) seems not to have been established, though there were no negative effects (398) , and ERG improved oocyte quality and maturation in cows and sheep (399) . ERG is also present in eye lens, where its concentration is lower in individuals with cataracts (400) .…”
Section: Serum and Other Concentrationsmentioning
confidence: 99%
“…Interestingly, ERG is also present in seminal fluid (394)(395)(396) and human breast milk (6) . Any possible correlation with male fertility (397) seems not to have been established, though there were no negative effects (398) , and ERG improved oocyte quality and maturation in cows and sheep (399) . ERG is also present in eye lens, where its concentration is lower in individuals with cataracts (400) .…”
Section: Serum and Other Concentrationsmentioning
confidence: 99%
“…Several studies have also reported that there is a role for the immune system during pregnancy reacting against and/or tolerating the paternal antigens of the conceptus [68][69][70][71][72][73][74]. It was suggested that that increased exposure to the father's semen assists this immunological tolerance [68]. In addition to these benefits, although semen is not sterile, microbial tolerance mechanisms may exist [75].…”
Section: Activation Of Inflammasomes In Preeclampsia-affected Pregnanmentioning
confidence: 99%
“…In addition to these benefits, although semen is not sterile, microbial tolerance mechanisms may exist [75]. Recent reports [68,75] have shown evidence that semen may be responsible for inoculating the developing conceptus, including the placenta with microbes, not all of which are infectious. It was suggested that when they are infectious, it may cause PE [68].…”
Section: Activation Of Inflammasomes In Preeclampsia-affected Pregnanmentioning
confidence: 99%
“…For example, PE is reported to be more prevalent in patients with pre‐existing periodontitis . In addition, semen is far from sterile and commonly infected with microbes, which might be the origin of infection associated with PE . Furthermore, studies have shown the presence of microbes in the placenta, amniotic fluid and vagina, and these bacteria vary greatly in PE .…”
Section: Innate Immunitymentioning
confidence: 99%